Analyzing the Existence of Momentum and Reversal Effects in Colombo Stock Exchange - Mithila, G (Faculty of Management and Finance, University of Colombo, 2025)
This study reexamines the existence of momentum and reversal effects in the Colombo Stock Exchange over the period from January 2015 to March 2024. The sample consists of 261 voting stocks listed on the main board, with firms having less than 12 months of data excluded. The analysis is motivated by recent structural changes in the CSE, including increased retail participation, post-crisis volatility and evolving market microstructure, which may affect the persistence of return anomalies. After cleaning the data, zero cost long short portfolios were constructed using various formations and holding periods. From 2015 to 2019, momentum and contrarian strategies produced negative and statistically insignificant returns. Even extreme (1% and 5%) and broader splits (25% and 30%) failed to deliver reliable performance. Shorter term strategies (3 and 6 months) produced smaller losses, while 12-month strategies incurred larger declines, highlighting the market’s inability to sustain momentum. Findings from 2020 to 2024 reconfirm the earlier pattern. Of 96 portfolios tested, only 19 showed statistical significance, most with negative returns. Winner portfolios often underperformed relative to loser portfolios. While a few strategies revealed stronger momentum, their returns remained mostly negative. Overall, the lack of consistent performance across all strategies suggests that traditional momentum and reversal approaches are ineffective in the Sri Lankan context. The results highlight the need for alternative models incorporating fundamental factors, machine learning approaches to better understand and potentially exploit the market inefficiencies.
Keywords: Market inefficiency; Zero cost portfolios; Sri Lankan stock market; Reversal effect; Momentum effect